The Genomic Signature of Demographic Decline in a Long‐Distance Migrant in a Range‐Extreme Population - George Day; Thomas Bolderstone; Greg J. Conway; Tony Cross; Tony Davis; Matilda Dolan; Mervyn Greening; Colin Neale; Ian Nicholson; Kim Nicholson; Ann Ward; Nik Ward; et al. (Molecular Ecology, 2025)
Migratory birds are inherently vagile, a strategy that may reduce the impacts of habitat loss and fragmentation on genetic diversity. However, specialist resource requirements and range‐edge distribution can counteract these benefits. The European nightjar ( Caprimulgus europaeus ) is a long‐distance migratory bird and resource specialist. Like other long‐distance migrants, nightjar populations have declined across the British Isles and Northwestern Europe over the past century. With this decline well documented in the British Isles, there is a need to quantify its genetic impacts. We applied full genome resequencing to 60 historic (1841–1980) and 36 contemporary British nightjars. Nightjars exhibited a statistically significant 34.8% loss in heterozygosity and an increase in inbreeding over the last ~180 years, showing a departure from panmixia towards weak spatial structure in the modern population. Such fine‐scale structuring in migratory birds is rare. Our results provide a case study of fragmentation's impact on a species with specialist resource requirements at its range limit. Similar demographic declines in nightjars and other long‐distance migrants across Northern and Western Europe suggest that genetic patterns seen in the British population may reflect those in other nightjar populations and European avifauna. Whilst our results indicate no immediate conservation concern, they depict a trajectory of declining genetic diversity, increasing inbreeding and genetic structure, potentially shared with other migratory species. Our study highlights the value of applying spatiotemporal population genetics analysis to migratory birds, despite their inherent vagility.

The cleanability of laser etched surfaces with repeated fouling using Staphylococcus aureus and milk - Kathryn Whitehead; Lisa I. Pilkington; Anthony J. Slate; Fabien Saubade; Mohsin Amin; Adrian Lutey; Laura Gemini; Rainer Kling; Luca Romoli (Food and Bioproducts Processing, 2023)

Ionic gold demonstrates antimicrobial activity against Pseudomonas aeruginosa strains due to cellular ultrastructure damage - Miguel Reyes Torres; Anthony J. Slate; Steven F. Ryder; Maliha Akram; Conrado Javier Carrascosa Iruzubieta; Kathryn A. Whitehead (Archives of Microbiology, 2021)
Due to the ever-increasing rise of antimicrobial resistant (AMR) bacteria, the development of alternative antimicrobial agents is a global priority. The antimicrobial activity of ionic gold was explored against four Pseudomonas aeruginosa strains with different AMR profiles in order to determine the antimicrobial activity of ionic gold and elucidate the mechanisms of action. Disc diffusion assays (zone of inhibition: ZoI) coupled with minimum inhibitory/bactericidal concentrations (MIC/MBC) were conducted to determine the antimicrobial efficacy of ionic gold. Scanning electron microscopy (SEM) was used to visualise morphological changes to the bacterial cell ultrastructure. Strains with increased AMR were slower to grow which is likely a fitness cost due to the enhanced AMR activity. Although greater concentrations of ionic gold were required to promote antimicrobial activity, ionic gold demonstrated similar antimicrobial values against all strains tested. Lowry assay results indicated that protein leakage was apparent following incubation with ionic gold, whilst SEM revealed cellular ultrastructure damage. This study suggests that the application of ionic gold as an alternative antimicrobial is promising, particularly against AMR P. aeruginosa . The antimicrobial activity of ionic gold against P. aeruginosa could potentially be utilised as an alternative therapeutic option in wound management, an approach that could benefit healthcare systems worldwide.

Social and spatial effects on genetic variation between foraging flocks in a wild bird population - Reinder Radersma; Colin J. Garroway; Anna W. Santure; Isabelle de Cauwer; Damien R. Farine; Jon Slate; Ben C. Sheldon (Molecular Ecology, 2017)
Social interactions are rarely random. In some instances, animals exhibit homophily or heterophily, the tendency to interact with similar or dissimilar conspecifics, respectively. Genetic homophily and heterophily influence the evolutionary dynamics of populations, because they potentially affect sexual and social selection. Here, we investigate the link between social interactions and allele frequencies in foraging flocks of great tits ( Parus major ) over three consecutive years. We constructed co‐occurrence networks which explicitly described the splitting and merging of 85,602 flocks through time (fission–fusion dynamics), at 60 feeding sites. Of the 1,711 birds in those flocks, we genotyped 962 individuals at 4,701 autosomal single nucleotide polymorphisms ( SNP s). By combining genomewide genotyping with repeated field observations of the same individuals, we were able to investigate links between social structure and allele frequencies at a much finer scale than was previously possible. We explicitly accounted for potential spatial effects underlying genetic structure at the population level. We modelled social structure and spatial configuration of great tit fission–fusion dynamics with eigenvector maps. Variance partitioning revealed that allele frequencies were strongly affected by group fidelity (explaining 27%–45% of variance) as individuals tended to maintain associations with the same conspecifics. These conspecifics were genetically more dissimilar than expected, shown by genomewide heterophily for pure social (i.e., space‐independent) grouping preferences. Genomewide homophily was linked to spatial configuration, indicating spatial segregation of genotypes. We did not find evidence for homophily or heterophily for putative socially relevant candidate genes or any other SNP markers. Together, these results demonstrate the importance of distinguishing social and spatial processes in determining population structure.

Effect of Mechanical Strain on Solute Diffusion in Human TMJ Discs: An Electrical Conductivity Study - Gregory J. Wright; Jonathan Kuo; Changcheng Shi; Thierry R. H. Bacro; Elizabeth H. Slate; Hai Yao (Annals of Biomedical Engineering, 2013)

Large-scale isolation of Eastern spiny mouse Acomys dimidiatus microsatellite loci through GS-FLX 454 titanium sequencing - Sanad Alfadala; Deborah A. Dawson; Gavin J. Horsburgh; Jerzy M. Behnke; Anna Bajer; Eman M. E. Mohallal; Samy Zalat; Jon Slate (Conservation Genetics Resources, 2013)

Detecting genes for variation in parasite burden and immunological traits in a wild population: testing the candidate gene approach - E. A. Brown; J. G. Pilkington; D. H. Nussey; K. A. Watt; A. D. Hayward; R. Tucker; A. L. Graham; S. Paterson; D. Beraldi; J. M. Pemberton; J. Slate (Molecular Ecology, 2013)
Identifying the genes underlying phenotypic variation in natural populations can provide novel insight into the evolutionary process. The candidate gene approach has been applied to studies of a number of traits in various species, in an attempt to elucidate their genetic basis. Here, we test the application of the candidate gene approach to identify the loci involved in variation in gastrointestinal parasite burden, a complex trait likely to be controlled by many loci, in a wild population of S oay sheep. A comprehensive literature review, G ene O ntology databases, and comparative genomics resources between cattle and sheep were used to generate a list of candidate genes. In a pilot study, these candidates, along with 50 random genes, were then sequenced in two pools of S oay sheep; one with low gastrointestinal nematode burden and the other high, using a N imble G en sequence capture experiment. Further candidates were identified from single nucleotide polymorphisms ( SNP s) that were highly differentiated between high‐ and low‐resistance sheep breeds. A panel of 192 candidate and control SNP s were then typed in 960 individual S oay sheep to examine whether they individually explained variation in parasite burden, as measured as faecal egg count, as well as two immune measures ( T eladorsagia circumcincta ‐specific antibodies and antinuclear antibodies). The cumulative effect of the candidate and control SNP s were estimated by fitting genetic relationship matrices ( GRM s) as random effects in animal models of the three traits. No more significant SNP s were identified in the pilot sequencing experiment and association study than expected by chance. Furthermore, no significant difference was found between the proportions of candidate or control SNP s that were found to be significantly associated with parasite burden/immune measures. No significant effect of the candidate or control gene GRM s was found. There is thus little support for the candidate gene approach to the identification of loci explaining variation in parasitological and immunological traits in this population. However, a number of SNP s explained significant variation in multiple traits and significant correlations were found between the proportions of variance explained by individual SNP s across multiple traits. The significant SNP s identified in this study may still, therefore, merit further investigation.

Selection and microevolution of coat pattern are cryptic in a wild population of sheep - J. GRATTEN; J. G. PILKINGTON; E. A. BROWN; T. H. CLUTTON‐BROCK; J. M. PEMBERTON; J. SLATE (Molecular Ecology, 2012)
Understanding the maintenance of genetic variation in natural populations is a core aim of evolutionary genetics. Insight can be gained by quantifying selection at the level of the genotype, as opposed to the phenotype. Here, we show that in a natural population of Soay sheep which is polymorphic for coat pattern, recessive genetic variants at the causal gene, agouti signalling protein ( ASIP ) are associated with reduced lifetime fitness. This was due primarily to a reduction in juvenile survival of uniformly coloured (self‐type) sheep, which are homozygous recessive, and occurs despite significantly higher reproductive success in surviving self‐type adults. Consistent with their relatively low fitness, we show that the frequency of self‐type individuals has declined from 1985 to 2008. Remarkably though, the frequency of the underlying self‐allele has increased, because the frequency of heterozygous individuals (who harbour the majority of all self‐alleles) has increased. Indeed, the ratio of observed/expected heterozygous individuals has increased during the study, such that there is now a significant excess of heterozygotyes. By employing gene‐dropping simulations, we show that microevolutionary trends in the frequency and excess of ASIP heterozygotes are too pronounced to be caused by genetic drift. Studying this polymorphism at the level of phenotype rather than underlying genotype would have failed to detect cryptic fitness differences. We would also have been unable to rule out genetic drift as an evolutionary force driving genetic change. This highlights the importance of resolving the underlying genetic basis of phenotypic variation in explaining evolutionary dynamics.

Corrigendum - J. R. CHAPMAN; S. NAKAGAWA; D. W. COLTMAN; J. SLATE; B. C. SHELDON (Molecular Ecology, 2011)

A quantitative review of heterozygosity–fitness correlations in animal populations - J. R. CHAPMAN; S. NAKAGAWA; D. W. COLTMAN; J. SLATE; B. C. SHELDON (Molecular Ecology, 2009)
The ease of obtaining genotypic data from wild populations has renewed interest in the relationship between individual genetic diversity and fitness‐related traits (heterozygosity–fitness correlations, or HFC). Here we present a comprehensive meta‐analysis of HFC studies using powerful multivariate techniques which account for nonindependence of data. We compare these findings with those from univariate techniques, and test the influence of a range of factors hypothesized to influence the strength of HFCs. We found small but significantly positive effect sizes for life‐history, morphological, and physiological traits; while theory predicts higher mean effect sizes for life‐history traits, effect size did not differ consistently with trait type. Newly proposed measures of variation were no more powerful at detecting relationships than multilocus heterozygosity, and populations predicted to have elevated inbreeding variance did not exhibit higher mean effect sizes. Finally, we found evidence for publication bias, with studies reporting weak, nonsignificant effects being under‐represented in the literature. In general, our review shows that HFC studies do not generally reveal patterns predicted by population genetic theory, and are of small effect (less than 1% of the variance in phenotypic characters explained). Future studies should use more genetic marker data and utilize sampling designs that shed more light on the biological mechanisms that may modulate the strength of association, for example by contrasting the strength of HFCs in mainland and island populations of the same species, investigating the role of environmental stress, or by considering how selection has shaped the traits under investigation.

Patterns of linkage disequilibrium in mitochondrial DNA of 16 ruminant populations - J. Slate; S. H. Phua (Molecular Ecology, 2003)
Mitochondrial DNA (mtDNA) is a widely employed molecular tool in phylogeography, in the inference of human evolutionary history, in dating the domestication of livestock and in forensic science. In humans and other vertebrates the popularity of mtDNA can be partially attributed to an assumption of strict maternal inheritance, such that there is no recombination between mitochondrial lineages. The recent demonstration that linkage disequilibrium (LD) declines as a function of distance between polymorphic sites in hominid mitochondrial genomes has been interpreted as evidence of recombination between mtDNA haplotypes, and hence nonclonal inheritance. However, critics of mtDNA recombination have suggested that this association is an artefact of an inappropriate measure of LD or of sequencing error, and subsequent studies of other populations have failed to replicate the initial finding. Here we report the analysis of 16 ruminant populations and present evidence that LD significantly declines with distance in five of them. A meta‐analysis of the data indicates a nonsignificant trend of LD declining with distance. Most of the earlier criticisms of patterns between LD and distance in hominid mtDNA are not applicable to this data set. Our results suggest that either ruminant mtDNA is not strictly clonal or that compensatory selection has influenced patterns of variation at closely linked sites within the mitochondrial control region. The potential impact of these processes should be considered when using mtDNA as a tool in vertebrate population genetic, phylogenetic and forensic studies.

Kinetics of isomerization for the proline helical forms of two oligoproline redox arrays by circular dichroic spectropolarimetry - Cheryl A. Slate; Robert A. Binstead; Thomas J. Meyer; Bruce W. Erickson (International Journal of Peptide Research and Therapeutics, 1999)

Statistical confidence for likelihood‐based paternity inference in natural populations - T. C. MARSHALL; J. SLATE; L. E. B. KRUUK; J. M. PEMBERTON (Molecular Ecology, 1998)
Paternity inference using highly polymorphic codominant markers is becoming common in the study of natural populations. However, multiple males are often found to be genetically compatible with each offspring tested, even when the probability of excluding an unrelated male is high. While various methods exist for evaluating the likelihood of paternity of each nonexcluded male, interpreting these likelihoods has hitherto been difficult, and no method takes account of the incomplete sampling and error‐prone genetic data typical of large‐scale studies of natural systems. We derive likelihood ratios for paternity inference with codominant markers taking account of typing error, and define a statistic Δ for resolving paternity. Using allele frequencies from the study population in question, a simulation program generates criteria for Δ that permit assignment of paternity to the most likely male with a known level of statistical confidence. The simulation takes account of the number of candidate males, the proportion of males that are sampled and gaps and errors in genetic data. We explore the potentially confounding effect of relatives and show that the method is robust to their presence under commonly encountered conditions. The method is demonstrated using genetic data from the intensively studied red deer ( Cervus elaphus ) population on the island of Rum, Scotland. The Windows‐based computer program, CERVUS , described in this study is available from the authors. CERVUS can be used to calculate allele frequencies, run simulations and perform parentage analysis using data from all types of codominant markers.